If it's not what You are looking for type in the equation solver your own equation and let us solve it.
35-13=x
We move all terms to the left:
35-13-(x)=0
We add all the numbers together, and all the variables
-1x+22=0
We move all terms containing x to the left, all other terms to the right
-x=-22
x=-22/-1
x=+22
| 16x-15-99=13 | | 60+20s=285 | | -5v+11=8 | | 7x-3(x-8=50(8x+2) | | 57=2(3+r) | | 3(5x−4)^2−25=2 | | 3b+11=5 | | 2x+6x–10=6 | | 2(16+w)=56 | | 10=4/5n-10 | | 2x+6x–10=6 | | 110y+10-11y=1 | | H(t)=-16t^2+40t+15 | | 2a-3=-5 | | 7x-3(x-8=1/2(8x+2) | | .4d+3.1=12.3 | | 8x-25=83 | | 0.04=25x | | (3x/10)+(4x/5)=11 | | –3s+8=4−2s | | 43=4.15/(.12-x) | | 27-3s=15 | | 8.33x=3.33x+40 | | -2x+3+5x=-9 | | -6-5(7b+5)=-171 | | -6x-6-2x=26 | | 0.25(x+4)–3=28 | | 12-6t=15 | | -2+2x+12=10 | | 0.48=0.8x | | y=8.25 | | 10+5x-6x=4 |